Testing effects of Lorentz invariance violation in the propagation of astroparticles with the Pierre Auger Observatory - The Pierre Auger Collaboration; Rovero, Adrian Carlos; Scornavacche, Marina Andrea; Perlin, Matias; González, Nicolás Martín; Botti, Ana Martina; Gollan Scilipotti, Fernando Daniel; Figueira, Juan Manuel; Supanitsky, Alberto Daniel; Gesualdi, Flavia; Cobos Cerutti, Agustin Cleto; Mariazzi, Analisa Gabriela; et al. (IOP Publishing, 2022)
Fil: The Pierre Auger Collaboration. The Pierre Auger Observatory; Estados Unidos